Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1136/bmjopen-2019-032705
|View full text |Cite|
|
Sign up to set email alerts
|

Randomised controlled pilot feasibility trial of an early intervention programme for young infants with neurodevelopmental impairment in Uganda: a study protocol

Abstract: IntroductionEarly intervention programmes (EIPs) for infants with neurodevelopmental impairment have been poorly studied especially in low-income settings. We aim to evaluate the feasibility and acceptability of a group participatory EIP, the ‘ABAaNA EIP’, for young children with neurodevelopmental impairment in Uganda.Methods and analysisWe will conduct a pilot feasibility, single-blinded, randomised controlled trial comparing the EIP with standard care across two study sites (one urban, one rural) in central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The feasibility trial was a two-centre, single blind, randomized controlled trial with two parallel groups to evaluate this participatory, group, early care and support programme compared to standard care. The trial methodology has been previously described [ 30 ] and the findings reported [ 29 ]. Trial participants were young children (6–11 months of age) with neurodevelopmental impairment (NDI) consistent with a diagnosis of developmental disability and their caregivers, from two sites in Uganda: Mulago Hospital, the National Referral Hospital in Kampala; and Kiwoko Hospital in Nakaseke District, central Uganda [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The feasibility trial was a two-centre, single blind, randomized controlled trial with two parallel groups to evaluate this participatory, group, early care and support programme compared to standard care. The trial methodology has been previously described [ 30 ] and the findings reported [ 29 ]. Trial participants were young children (6–11 months of age) with neurodevelopmental impairment (NDI) consistent with a diagnosis of developmental disability and their caregivers, from two sites in Uganda: Mulago Hospital, the National Referral Hospital in Kampala; and Kiwoko Hospital in Nakaseke District, central Uganda [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…The trial methodology has been previously described [ 30 ] and the findings reported [ 29 ]. Trial participants were young children (6–11 months of age) with neurodevelopmental impairment (NDI) consistent with a diagnosis of developmental disability and their caregivers, from two sites in Uganda: Mulago Hospital, the National Referral Hospital in Kampala; and Kiwoko Hospital in Nakaseke District, central Uganda [ 30 ]. Recruited children were 6–11 months of age and were followed to 18–23 months.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this challenge, in 2019, the PDC program integrated early intervention using the Baby Ubuntu model [48], a group participatory early intervention program starting from 6 months for young children with disability and their families. The 10-module, participatory, parents' peer support group program includes a module designed to provide caregivers with skills to appropriately feed a child with a disability and manage their feeding difficulties at home [49,50].…”
Section: Plos Onementioning
confidence: 99%
“…They also show the feasibility of facilitation by a professional and a caregiver [38]. A randomized controlled trial evaluation of Baby Ubuntu is forthcoming [39].…”
mentioning
confidence: 92%